Perbedaan Trust Pasangan Yang Menjalin Hubungan Jarak Jauh Ditinjau Dari Status Perkawinan - Nantasia Amandha, Tiyagita, Aad Satria Permadi, S.Psi, MA (2016)
This research aims to: 1) Know the difference trust distance relationship couples un-married (long-distance courtship) with a long distance relationship couples who are married (long-distance marriages) 2) Knowing the level of trust long distance relationship couples un-married (long-distance courtship) with a long distance relationship couples who are married (long-distance marriages). Subjects in this study were man or a woman young adults aged 18 to 40 years that un-married and married that is currently serving a long distance relationships. These research subjects are 80 of them are 40 people who are dating long distance and 40 long distance marriages.The sampling technique used was purposive sampling. Data collecting method using the scale trust pairs.This research data analysis techniques using the independent sample T-test.Based on test results independent sample t-test values obtained at t = -12.574 with coefficient sig. = 0.000 (p = <0.05) which means there is no difference between long-distance relationship pairs un-married (distance courtship away) with a long distance relationship pairs who are married (long distancemarriages).Subjects in this study has a levels of trust pairS are classified an equally high. Keywords: Trust pair, long-distance relationship, long-distance courtship, long-distance marriages